Experiential avoidance versus Decentering abilities: The role of different emotional processes on disordered eating - Mendes, A. L. (2016)
In modern Western societies, the female body is a predominantly used dimension in self and social evaluations. In fact, the perceived discrepancy between one´s current and ideal body image may act as a pathogenic phenomenon for women´s well-being. Furthermore, significant differences in the tendency to engage in disordered eating attitudes and behaviours have been verified between women sharing similar characteristics and perceptions about weight and body shape, which suggests that different emotion regulation processes may be involved in this association. This study thus aims to clarify the mediational effect of two different emotional regulation processes, experiential avoidance and decentering, on the association of weight and body shape variables and shame with disordered eating, in a sample of 760 women. The tested path model explained 44% of disordered eating attitudes and behaviours and showed an excellent model fit. Results demonstrated that Body Mass Index had a direct effect, albeit weak, on disordered eating behaviours and that body image discrepancy and shame presented indirect effects through the mechanisms of experiential avoidance and decentering. Results also revealed that experiential avoidance and decentering showed significant mediator effects on the relationship of weight and body shape and shame with disordered eating behaviors. These findings suggested that while experiential avoidance exacerbates the impact of weight and body shape and shame on disordered eating attitudes and behaviors, decentering seems to attenuate this association. Our findings appear to offer significant clinical and research implications, highlighting the importance of targeting maladaptive emotion processes through the development of decentering abilities.